The origins of redistributive policy preferences: political socialisation with and without a welfare state - Neundorf, Anja; Soroka, Stuart (Taylor & Francis, 2017)
Research on the impact of the macroeconomy on individual-level preferences for redistribution has produced varying results. This paper presents a new theory on the presence of an expansive welfare state during one’s formative years as a source of heterogeneity in the effect that macroeconomic conditions have on individuals’ preferences for redistributive policy. This theory is tested using cohort analysis via the British Social Attitudes surveys (1983–2010), with generations coming of age between the end of World War I and today. Findings confirm that cohorts that were socialised before and after the introduction of the welfare state react differently to economic crises: the former become less supportive of redistribution, while the latter become more supportive. The research sheds light on the long-term shifts of support for the welfare state due to generational replacement.